The Influence of Competence, Organizational Culture, Spiritual Leadership on Organizational Behavior and Its Impact on Lecturer Performance at Higher Education in Baubau City - hardin h; Azelia Monica Azizu; Wa Ode Dian Purnama Sari (Institute for Research and Community Service, 2020)
Lecturer performance is closely related to various factors such as inadequate competence of lecturers, weak organizational culture, low spiritual leadership and organizational behavior that is not suitable for improving lecturer performance. The objectives of this study are: (1) Testing and analyzing the positive and significant influence between lecturer competence, academic culture, spiritual leadership and organizational behavior simultaneously on lecturer performance; (2) Testing and analyzing the positive and significant influence between lecturer competence on lecturer performance; (3) Testing and analyzing the positive and significant influence between academic culture on lecturer performance; (4) Testing and analyzing the positive and significant influence between spiritual leadership on lecturer performance; (5) Testing and analyzing the positive and significant influence between organizational behavior on lecturer performance. The research method is a combination of sequential explanatory models or designs. The research sample was 140 lecturers. The data analysis in this study used multiple linear regression statistical analysis using the Social Sciences Program Statistics version 20. The results of this study were: (1) The simultaneous regression hypothesis was the Fcount of 254 and the Sig. shows that the probability value of 0.000 is smaller than 0.05, this means that the independent variables, namely lecturer competence, academic culture, spiritual leadership and organizational behavior simultaneously have a positive and significant effect on lecturer performance; (2) The value of tcount 2.271 > ttable 1.978 and the value of Sig. variable X2 0.025 < 0.05, it can be concluded that the variable competence of lecturers has a significant positive effect on lecturer performance; (3) The value of tcount -1.023 < ttable 1.978, and the value of Sig. variable X3 0.308 > 0.05, it can be concluded that the academic culture variable has an insignificant negative effect on lecturer performance; (4) The value of tcount -1.115 < ttable 1.978 and the value of Sig. variable X4 0.267 > 0.05, it can be concluded that the spiritual leadership variable has an insignificant negative effect on lecturer performance; (5) The value of tcount 16.896 > ttable 1.978 and the value of Sig. variable X5 0.00 < 0.05, it can be concluded that the variable organizational behavior has a significant positive effect on lecturer performance.